ALIH AKSARA DAN ALIH BAHASA TEKS KITAB FADHILAH SYUHUR MENERANGKAN KELEBIHAN BULAN MUHARRAM DAN KELEBIHAN HARI ASYURA DISUSUN OLEH IMAM MAULANA ABDUL MANAF AMIN AL-KHATIB - Tanjung, Riska Ardiana; Nasution, Bakhtarudin; Zulfadhli, Zulfadhli (Universitas Negeri Padang, 2017)
This article aims to: (a) presents a transliteration Kitab Fadhilah Syuhur Menerangkan Kelebihan Bulan Muharran and Kelebihan Hari Asyura arranged by Imam Maulana Abdul Manaf Amin Al-Khatib texts, and (b) serves over language Kitab Fadhilah Syuhur Menerangkan Kelebihan Bulan Muharran dan Kelebihan Hari Asyura arranged by Imam Maulana Abdul Manaf Amin Al-Khatib texts. The results of this study is to present a text that can be read and understood by the people now on the text of the Kitab Fadhilah Syuhur Menerangkan Kelebihan Bulan Muharram and Kelebihan Hari Asyura arranged by Imam Maulana Abdul Manaf Amin Al-Khatib. The results of this study also presents the text has been adapted to the Indonesian Spelling (EBI). This text recounts every good practices such as fasting, charity, and the other was in the month of Muharram and Ashura, the reward will be multiplied practice. In the manuscript Kitab Fadhilah Syuhur Menerangkan Kelebihan Bulan Muharran and Kelebihan Hari Asyura arranged by Imam Maulana Abdul Manaf Amin Al-Khatib text is a vocabulary that shows the variety of old Malay language in it. This is done in order to maintain the purity of the language script.Keywords: transliteration, transcription, ancient script